Complement Alternative Pathway Deficiency in Recipients Protects Kidney Allograft From Ischemia/Reperfusion Injury and Alloreactive T Cell Response. Issue 9 (10th April 2017) - Casiraghi, F.; Azzollini, N.; Todeschini, M.; Fiori, S.; Cavinato, R. A.; Cassis, P.; Solini, S.; Pezzuto, F.; Mister, M.; Thurman, J. M.; Benigni, A.; Remuzzi, G.; et al.
Abstract : Despite the introduction of novel and more targeted immunosuppressive drugs, the long‐term survival of kidney transplants has not improved satisfactorily. Early antigen‐independent intragraft inflammation plays a critical role in the initiation of the alloimmune response and impacts long‐term graft function. Complement activation is a key player both in ischemia/reperfusion injury (IRI) as well as in adaptive antigraft immune response after kidney transplantation. Since the alternative pathway (AP) amplifies complement activation regardless of the initiation pathways and renal IR injured cells undergo uncontrolled complement activation, we speculated whether selective blockade of AP could be a strategy for prolonging kidney graft survival. Here we showed that Balb/c kidneys transplanted in factor b deficient C57 mice underwent reduced IRI and diminished T cell–mediated rejection. In in vitro studies, we found that fb deficiency in T cells and dendritic cells conferred intrinsic impaired alloreactive/allostimulatory functions, respectively, both in direct and indirect pathways of alloantigen presentation. By administering anti‐fB antibody to C57 wt recipients in the early post Balb/c kidney transplant phases, we documented that inhibition of AP during both ischemia/reperfusion and early adaptive immune response is necessary for prolonging graft survival. These findings may have implication for the use of AP inhibitors in clinical kidney transplantation. Abstract : Kidney allografts transplanted in either complement factor b –deficient mice or wild‐type mice given an anti‐ factor b antibody show reduced ischemia/reperfusion injury, mitigated T cell alloimmune response, and prolonged survival.